2006
DOI: 10.1134/s0021364006200112
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal NMR and spin states in the A-like phase of 3He in aerogel

Abstract: It was found that two different spin states of the A-like phase can be obtained in aerogel sample. In one of these states we have observed the signal of the longitudinal NMR, while in another state no trace of such a signal was found. The states also have different properties in transverse NMR experiments. Longitudinal NMR signal was also observed in the B-like phase of 3 He in aerogel.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(52 citation statements)
references
References 13 publications
6
46
0
Order By: Relevance
“…82) NMR experiments have been performed on 3 He in 97.5% aerogel which support the view that the metastable A-like phase is in fact a robust state, 83) but other measurements 16,66) appear to have inconsistencies with this interpretation.…”
Section: Superfluidmentioning
confidence: 62%
See 1 more Smart Citation
“…82) NMR experiments have been performed on 3 He in 97.5% aerogel which support the view that the metastable A-like phase is in fact a robust state, 83) but other measurements 16,66) appear to have inconsistencies with this interpretation.…”
Section: Superfluidmentioning
confidence: 62%
“…In both cases the spectra are complex owing to a distribution of textures and, in the latter case, coexistence of these two phases in different parts of their aerogel sample. Direct observation of the longitudinal resonance frequency has also been reported by this group in both phases 66) as well as observation 67) of a homogeneous precession domain (HPD) in the aerogel B-phase. Sato et al 15) have observed HPD in an ESP-state of superfluid 3 He for the first time using aerogel.…”
Section: )mentioning
confidence: 92%
“…For example, in the bi-axial OG-SN state with l 2 z ≈ 1/3, and l 2 x = l 2 y for µ=0 one gets ∆ω ∝ (1 + cos β). Such dependence was observed in weakly anisotropic aerogel samples in [27,26,10].…”
Section: Two States Ofmentioning
confidence: 87%
“…Earlier it was found [26,22] that the A-like phase may exist in two states. One state is obtained if on cooling through T ca the low level of RF (or no RF) is used.…”
Section: Continuous Wave Nmr Experimentsmentioning
confidence: 99%
“…Previously the small negative frequency shift has been observed in some samples of aerogel [19,20], which can be explained by a residual deformations of these samples.…”
mentioning
confidence: 99%